THE EFFECT OF USING ENGLISH CARTOON MOVIE TOWARD STUDENTS’ LISTENING COMPREHENSION AT GRADE X SMAN 1 TEMBILAHAN - Wati, Rinda Yuliana; Yeni, Melda; Syafrizal (Program Studi Pendidikan Bahasa Inggris, 2023)
This study aimed at measuring the effectiveness of using English cartoon movies towards students listening comprehension in tenth grade at SMAN 1 Tembilahan. The study included quasi-experimental design, especially a non-randomized control group, a pre-test, and a post-test. The researcher designed the lesson plan, conducted the treatment, and observed the students' scores by pre-test and post-test. The population of study was the tenth graders of SMAN 1 Tembilahan, which consisted of two classes with 47 students. The researchers chose X MIPA 3 as the control class and X MIPA 2 as the experiment class, which are both samples. The sample was determined using the purposive sampling technique. The researcher applied the T-test calculation to test the hypothesis and analyze the data. The result of the T-test using manual calculation found t-observed (10,767) and t-table at a significance level of 5% (1,6793). It meant t-observed > t-table. It was interpreted that the alternative hypotheses (Ha) stating there is a significant effect of English cartoon movies on students’ listening comprehension at the tenth grade level of SMAN 1 Tembilahan were accepted and the null hypotheses (Ho) stating there is no significant effect of English cartoon movies on students’ listening comprehension at the tenth grade level of SMAN 1 Tembilahan were rejected. It was proved that the value of t-observed was higher than t-table, either at significance level 5% It meant that teaching listening using English cartoon movies had a significant effect on students’ listening comprehension in tenth grade at SMAN 1 Tembilahan.